Gestión y administración de un laboratorio de ciencias naturales en la Universidad Técnica de Cotopaxi para la carrera de educación básica - Bejarano Torres, María Gregoria (2014)
Based on the proposed objective of this research work is: Management and Administration for a science Lab in the School of Basic Education, Technical University of Cotopaxi, in academic institutions that are aimed at training students of Basic Education , have said that the absence of a laboratory, it is difficult to interrelate theory and practice, so it is urgent to implement a Science Lab that allows students to observe and analyze the object of study, and solve an urgent need for help to perform well. The methodology in this research was descriptive, because we used inductive and deductive methods. The contribution of the laboratory in the teaching-learning process in which applied: an interview with authorities, teachers and students with survey implementation allowed us to compile statistics and thus resolving the problem. From the above mentioned has concluded that management and administration is very It important in the laboratory for Best Performance in Basic Education Career also help us to strengthen and students` learning of the Technical University of Cotopaxi.